The Dynamics of Special Interests Development in Autistic Student - Thalia Ayu Rini (JPK (Jurnal Pendidikan Khusus), 2019)
The purpose of this case study was to describe the dynamics of special interests development in an autistic student at Dian Amanah Special School Yogyakarta. This study collected data about: 1) form of special interests; 2) model of interest’s development; 3) and consequence of special interests. Data were collected by observation, interview, and documentation technique. Data were analyzed data reduction, data display, and drawing conclusion/verification. The results showed 1) subject has 2 form of special interests on music and people; 2) special interests on music triggered by family and persisted by maintenance factor such as environmental opportunity, perception of ability, cognitive reward, and emotional reward while special interests on people triggered by other interests and persisted by maintenance factor such as environmental opportunity, cognitive reward, and emotional reward; 3) special interests on music viewed positively because there was perception of ability while SI on people viewed negatively due to behavioral problem.